Alzheimer's disease‐associated TREM2 variants exhibit either decreased or increased ligand‐dependent activation. Issue 4 (9th August 2016) - Song, Wilbur; Hooli, Basavaraj; Mullin, Kristina; Jin, Sheng Chih; Cella, Marina; Ulland, Tyler K.; Wang, Yaming; Tanzi, Rudolph E.; Colonna, Marco
Abstract : Introduction: TREM2 is a lipid‐sensing activating receptor on microglia known to be important for Alzheimer's disease (AD), but whether it plays a beneficial or detrimental role in disease pathogenesis is controversial. Methods: We analyzed AD risk of TREM2 variants in the NIMH AD Genetics Initiative Study and AD Sequencing Project. We compared each variant's risk and functional impact by a reporter assay. Finally, we analyzed expression of TREM2 on human monocytes. Results: We provide more evidence for increased AD risk associated with several TREM2 variants, and show that these variants decreased or markedly increased binding to TREM2 ligands. We identify HDL and LDL as novel TREM2 ligands. We also show that TREM2 expression in human monocytes is minimal compared to monocyte‐derived dendritic cells. Discussion: Our results suggest that TREM2 signaling helps protect against AD but can cause harm in excess, supporting the idea that proper TREM2 function is important to counteract disease progression.